Characteristics of T-lymphocyte subsets in patients with severe fever with thrombocytopenia syndrome complicated with invasive pulmonary aspergillosis: a retrospective study - Xu, Ying; Liu, Yang; Qian, Yajun; Liu, Ning; Tang, Jian; Dong, Danjiang; Xia, Mao; Wu, Weiwei; Gu, Qin (Frontiers in Immunology, 2026)
ObjectivesImmunosuppressed patients often acquire invasive pulmonary aspergillosis (IPA). In recent years, the incidence of patients with severe fever with thrombocytopenia syndrome (SFTS) complicated with IPA has increased. This study aimed to investigate the characteristics of the counts of T-lymphocyte subsets in patients with SFTS combined with IPA and explore their predictive value for IPA infection in SFTS patients.MethodsWe conducted a retrospective review of all patients with SFTS admitted to Nanjing Drum Tower Hospital between January 2016 and August 2022. The patients were divided into IPA and the non-IPA group. Clinical symptoms, laboratory findings, comorbidities, and overall prognosis were collected. Transcriptome sequencing was performed on six of the samples.ResultsA total of 99 SFTS patients were included, of whom 21 (21.2%) developed IPA. The 28-day mortality rate (33.3%) was higher in the IPA group than in the non-IPA group. The IPA group had a significant decrease in the absolute counts of total lymphocytes and CD4+ T lymphocytes and an increase in the ratio of CD4/CD8 T lymphocytes. ROC curves showed that the sensitivity and specificity for predicting the occurrence of IPA in SFTS patients was 50% and 95%, respectively, when the cut-off value for CD4+ T lymphocytes was 386 cells/μL. The transcriptome analysis revealed significant differences in host gene expression profiles between IPA and non-IPA groups, with notable enrichment in KEGG pathways related to metabolism, cellular functions, and systemic processes.ConclusionsPatients with an absolute count of CD4+ lymphocytes below 386 cells/μL are at risk of acquiring secondary IPA. It is necessary to screen the counts of T-lymphocyte subsets in SFTS patients after admission.